The impact of industrial zones on regional attractiveness and competitiveness in Algeria - Ferdj Younes (Studia Ekonomiczne i Regionalne)
Industrial zones in Algeria play a crucial role in shaping the attractiveness and competitiveness of the country’s regions. The impact of these zones extends beyond economic factors, influencing the overall appeal and competitive edge of different regions. Understanding the dynamics of industrial zones is essential for comprehending Algeria’s economic landscape and its efforts to enhance regional development. The primary objective of this article is to shed light on industrial zones and their impacts on regional industrial attractiveness and competitiveness in Algeria. Firstly, it involves clarifying the concept of regional attractiveness and competitiveness in relation to their economic, environmental, and social dimensions. This leads us, secondly, to examine non-institutional actors, specifically companies, and their interactions with their regions, based on an understanding of the local area, including the effect of industrial zones on the attractiveness and competitiveness of local companies.